1993
DOI: 10.1021/jm00068a001
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant activities of some arylsemicarbazones displaying potent oral activity in the maximal electroshock screen in rats accompanied by high protection indices

Abstract: Various semicarbazones derived from aryl aldehydes, phenylalkyl aldehydes, and phenylalkyl ketones as well as some related compounds were evaluated for anticonvulsant activity. Most of the compounds displayed anticonvulsant activity in the maximal electroshock (MES) and subcutaneous pentylenetetrazole (scPTZ) screens accompanied by neurotoxicity when given to mice by the intraperitoneal route. However quantitative data revealed protection indices (TD50/ED50) of less than 4 in general. Oral administration of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 7 publications
0
32
0
2
Order By: Relevance
“…In 1993 and 1996, Dimmock et al (1993;1996) reported on (aryloxy)aryl semicarbazones as compounds with potent anticonvulsant activity in maximum electroshock-and pentylenetetrazole-induced seizure models in rodents. These compounds did not have obvious structural similarities with classical anticonvulsants, and their mechanism of action was not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1993 and 1996, Dimmock et al (1993;1996) reported on (aryloxy)aryl semicarbazones as compounds with potent anticonvulsant activity in maximum electroshock-and pentylenetetrazole-induced seizure models in rodents. These compounds did not have obvious structural similarities with classical anticonvulsants, and their mechanism of action was not known.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds did not have obvious structural similarities with classical anticonvulsants, and their mechanism of action was not known. Initial binding experiments suggested interactions with g-aminobutyric acid (GABA)-gated Cl À channels (Dimmock et al, 1993). However, these effects were only seen at high concentrations, and subsequent experiments revealed no positive modulation of native or recombinant GABA A channels expressed in Xenopus oocytes (E.R.…”
Section: Introductionmentioning
confidence: 99%
“…A few compounds (50) with p-nitrophenyl substitution also showed activity in ScSTY tests. Acetophenone semicarbazone (73) and phenyl acetaldehyde semicarbazone (73) protected against seizures induced by ScPTZ (ED 50 60.75 mg kg -1 ) and subcutaneous bicuculline (ScBIC) (ED 50 57.63 mg kg -1 ) (Fig. 14).…”
Section: Mechanism Of Action Of Semicarbazone Anticonvulsantsmentioning
confidence: 97%
“…[24][25][26]33,38) It was suggested that (thio)semicarbazones anticonvulsant activity is mediated through GABA-mediated mechanism. 19,22,29,32,37,41) In the present investigation the two anticonvulsant candidates, chromones or flavones and thiosemicarbazones, were amalgamated to obtain more potent anticonvulsants compounds of series 1 and 2. In the synthesized hybrid compounds the chromone or the furochromone ring acts as the hydrophobic aryl ring required for binding which itself possesses anticonvulsant tendency.…”
mentioning
confidence: 99%